Primary cardiac tumours in a paediatric population: An experience from a tertiary centre with a review of literature - Narender Kumar; Shruti Sharma; Ruma Ray; Balram Airan (Wolters Kluwer Medknow Publications, 2014)
Background: To observe the histopathological spectrum of primary cardiac tumours in paediatric population those came in Pathology Department over a period of last 16 years. Materials and Methods: During the time period of 16 years (1995-2010), we had received 16 cases of primary cardiac tumours in paediatric patients. The tumour diagnosis and subtyping was done by histopathological examination along with cytochemistry and immunohistochemistry. Results: Benign cardiac tumours were much more common (15 cases) than the malignant tumours. Among these, myxoma was the most frequent (13 cases). The other benign cardiac tumours were rhabdomyoma (one case) and fibroma (one case). A primary malignant cardiac tumour was diagnosed in one case and was labelled as undifferentiated sarcoma. Conclusions: The present study reveals the pathological spectrum of surgically excised cardiac tumours in the paediatric population in northern India. Although the diagnosis of cardiac masses can be made by routine imaging techniques, but the role of pathologist is important for exact characterisation of tumour subtype.